Quantitative Detection of Borrelia burgdorferi in 2-Millimeter Skin Samples of Erythema Migrans Lesions: Correlation of Results with Clinical and Laboratory Findings - Liveris, Dionysios (American Society for Microbiology, 2002)
Variability of disease manifestations has been noted in patients with Lyme disease. A contributing factor to this variation may be the number of spirochetes present in infected patients. We evaluated clinical and laboratory findings for patients with erythema migrans with regard to the number of Borrelia burgdorferi organisms detected by quantitative PCR (qPCR) in 2-mm skin biopsy specimens. B. burgdorferi was detected in 80% (40 of 50) of the specimens tested; the mean number of spirochetes in these specimens ranged over 3 orders of magnitude (10 to 11,000 spirochetes per 2-mm biopsy specimen). Larger numbers of spirochetes were significantly associated with a shorter duration of the erythema migrans skin lesion (P = 0.020), smaller skin lesions (P = 0.020), and infection with a specific genotype of B. burgdorferi (P = 0.008) but not with the number or severity of symptoms. Skin culture positivity was significantly associated with skin lesions containing larger numbers of spirochetes (P = 0.019).